QOS on type-2 hypervisors in virtualized environment / Rukhiyah Adnan - Adnan, Rukhiyah (2014)
Virtualization has become a widely discussed topic nowadays, both for servers as well as for desktop systems. It involves the concepts of host operating system, guest (virtual) operating system and hypervisor. Hypervisor or Virtual Machines Monitor (VMM) is the machines where guest operating system resides. There are number of studies have been conducted in this field, especially those involving the hypervisor virtualization (Type-2). However, further research is needed in measuring network performance in terms of TCP Window Size, I/O file system performance and Web Server connectivity in virtualized environment; especially on another operating system such as Lubuntu 14.04, which is the lightest version of Ubuntu operating system. The objectives of the work is to determine a web server average successful connection lifetime from Lubuntu resides in hypervisors, to evaluate the network performance in terms of bandwidth (TCP), jitter (UDP) and changes in TCP window size; and to verify the performance of the results by measuring the I/O file system (1 MB, 32 MB, 512 MB, and 2 GB) in terms of read/write operation process. In this work, two test beds have been constructed; focusing on Intel based platform and AMD based platform. Benchmarking tools such as Iperf, Httperf and Iozone were installed inside virtual machines (Windows 7 and Lubuntu 14.04) reside in the type-2 hypervisors (VMware and VirtualBox). Overall, VMware performs better in terms of bandwidth, jitter (Lubuntu), web server average connection lifetime and I/O read operation compared to VirtualBox. In general, for both test bed, VMware consistently outperform VirtualBox in most aspect of the test done.